Honeycomb catalyst, reactor including honeycomb catalyst, and method for producing honeycomb catalyst
By adding a high thermal conductivity coating to the outer peripheral surface of the honeycomb catalyst and inserting a honeycomb catalyst into the reaction tube, the problem of coating hindering heat diffusion is solved, and efficient heat removal and reaction efficiency are achieved.
Patent Information
- Application Number
- JP2023123896
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-07
AI Technical Summary
In the prior art, the coating material of the honeycomb catalyst hinders the diffusion of the reaction heat, resulting in a decrease in reaction efficiency and deterioration of the catalyst performance.
A highly thermally conductive coating is provided on the outer peripheral surface of the honeycomb catalyst, using an amorphous oxide matrix containing SiC particles, improving the thermal conductivity of the coating, and inserting the honeycomb catalyst into the reaction tube to form an efficient heat removal system.
By increasing the heat removal efficiency, preventing the catalyst from overheating, improving the reaction efficiency and maintaining temperature stability in the reactor.
Smart Images

Figure 2025019957000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a honeycomb catalyst used in catalytic reactions such as methanation, a reactor using the honeycomb catalyst, and a method for manufacturing the honeycomb catalyst. [Background technology]
[0002] When attempting to harmlessly treat environmentally and biologically toxic exhaust gases containing carbon monoxide and carbon dioxide, or when attempting to convert them into useful substances such as hydrogen, hydrocarbons, and methane, it is known to appropriately use catalytic reactions using catalysts appropriate for the application.
[0003] One example of such a catalytic reaction is the methanation reaction (hereinafter also referred to as the methanation reaction) that synthesizes CH4 from CO2 and H2. The methanation reaction is a reaction that generates a large amount of heat, and the higher the temperature, the lower the methane conversion rate. For this reason, heat management to keep the catalyst temperature within an appropriate temperature range is important for the catalyst used in the methanation reaction. As an example of optimizing the reaction of such a catalyst, a heat exchanger reactor is known in which a coolant flows around a reaction tube packed with a catalyst to absorb the heat of reaction of the methanation reaction. Examples of catalysts that can be packed into the reaction tube include pellet-type catalysts and honeycomb catalysts. In particular, honeycomb catalysts have the advantage that they are easier to replace than pellet-type catalysts.
[0004] Patent Document 1 discloses a honeycomb structure in which a plurality of honeycomb segments are integrally bonded together with a bonding material, and the outer peripheral surface of the bonded body is covered with a coating material containing ceramics as a main component and also containing a granular filler and 9 to 13 mass % water, the granular filler imparting coatability and ductility to the coating material. Patent Document 1 claims that it is possible to provide a honeycomb structure with excellent durability in which the occurrence of defects such as small holes and cracks is reliably suppressed. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent Publication No. 2012-46417 Summary of the Invention [Problem to be solved by the invention]
[0006] However, a honeycomb catalyst covered with a coating material as in Patent Document 1 has problems in that the coating material hinders the diffusion of reaction heat, resulting in reduced reaction efficiency and catalyst deterioration. In view of the above problems, the present invention aims to provide a honeycomb catalyst with high heat removal efficiency that can appropriately maintain the temperature inside the reactor even with a conventional simple reactor configuration, a method for manufacturing the honeycomb catalyst, and a reactor using the honeycomb catalyst. [Means for solving the problem]
[0007] The inventors discovered that a method for improving the heat removal efficiency in conventional reactors is to provide a coating layer with high thermal conductivity on the outer peripheral surface of a honeycomb catalyst, and after extensive research into methods for improving the thermal conductivity of the coating layer, they came up with the present invention.
[0008] That is, a first embodiment of the present invention is a honeycomb catalyst comprising: a ceramic honeycomb structure having a plurality of through holes separated by partition walls; a catalytic component containing at least one of Ni, Fe, Co, Cu, and Ru supported on a surface of the partition walls; and a coating layer formed on an outer peripheral surface of the ceramic honeycomb structure, wherein the thermal conductivity of the coating layer is 1.5 W / [m·K] or more.
[0009] Here, in the honeycomb catalyst, the coating layer preferably comprises a matrix made of an amorphous oxide and SiC particles dispersed in the matrix. Furthermore, the amorphous oxide forming the matrix is preferably amorphous silica or amorphous alumina.
[0010] In addition, a second embodiment of the present invention is a reactor comprising: a ceramic honeycomb structure having a plurality of through holes separated by partition walls; a honeycomb catalyst having a catalyst component containing at least one of Ni, Fe, Co, Cu, and Ru supported on a surface of the partition walls, and a coating layer formed on an outer peripheral surface of the ceramic honeycomb structure, the coating layer having a thermal conductivity of 1.5 W / [m K] or more; and a reaction tube, in which the honeycomb catalyst is inserted into the reaction tube.
[0011] Here, it is preferable that a buffer material made of a copper nonwoven fabric is provided between the reaction tube and the honeycomb catalyst.
[0012] In addition, a manufacturing method for a honeycomb catalyst of the present invention is a manufacturing method for the above-mentioned honeycomb catalyst, which includes the steps of applying a slurry liquid containing an inorganic binder to a ceramic honeycomb structure formed by firing and having a plurality of flow holes separated by partition walls, applying a slurry liquid containing a catalytic component containing at least one of Ni, Fe, Co, Cu, and Ru, and then drying the resulting mixture to support the catalytic component on the partition walls, and applying a coating material comprising colloidal silica or colloidal alumina in which SiC particles are dispersed to the outer peripheral surface of the ceramic honeycomb structure on which the catalytic component is supported, to form a coating layer in which SiC particles are dispersed in amorphous silica or amorphous alumina. Effect of the Invention
[0013] The honeycomb catalyst provided by the present invention has a high heat removal efficiency and can easily dissipate the reaction heat in the reaction tube to the outside, which can prevent the inside of the honeycomb catalyst from being overheated, thereby contributing to improving the efficiency of the reactor. [Brief description of the drawings]
[0014] [Figure 1]FIG. 1A is a diagram showing a cross section perpendicular to the flow direction of a raw material gas, showing an embodiment of a honeycomb catalyst according to the present invention; FIG. 1B is a diagram showing a cross section parallel to the flow direction of a raw material gas, showing an embodiment of a honeycomb catalyst according to the present invention; and FIG. 1C is an enlarged view of a partition wall in an embodiment of a honeycomb catalyst according to the present invention. [Diagram 2] 1 is a diagram showing a cross section parallel to the flow direction of a raw material gas in one embodiment of a reactor according to the present invention. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, each embodiment of the present invention will be described in detail with reference to the drawings, but the present invention is not limited thereto. Furthermore, each configuration described in the present invention can be combined with each other as long as the function is not lost.
[0016] (Honeycomb catalyst) A first embodiment of the present invention is a honeycomb catalyst comprising: a ceramic honeycomb structure having a large number of through holes separated by porous partition walls; a catalytic component containing at least one of Ni, Fe, Co, Cu, and Ru supported on a surface of the partition walls; and a coating layer for sealing gas formed on an outer peripheral surface of the ceramic honeycomb structure, wherein the thermal conductivity of the coating layer is 1.5 W / [m·K] or more.
[0017] An example of a honeycomb catalyst of this embodiment is shown in Fig. 1. Fig. 1(a) is a diagram showing a cross section perpendicular to the flow direction of the raw material gas in the honeycomb catalyst 100, and Fig. 1(b) is a diagram showing a cross section parallel to the flow direction of the raw material gas in the honeycomb catalyst 100. The honeycomb catalyst 100 is composed of a columnar ceramic honeycomb structure 110, a coating layer 120, and a catalyst component 130. The ceramic honeycomb structure 110 has a structure in which a plurality of through holes 112 formed by being surrounded by porous partition walls 111 are arranged adjacent to each other so as to be parallel to the central axis of the ceramic honeycomb structure 110. In addition, a catalyst component 130 is supported on the surface of the partition walls 111. A coating layer 120 is formed on the outer peripheral surface of the ceramic honeycomb structure 110 to seal the ceramic honeycomb structure 110 so as to prevent leakage of the raw material gas therefrom.
[0018] FIG. 1( c ) is an enlarged view of a partition wall 111 in the honeycomb catalyst 100 . When such a honeycomb catalyst 100 is placed in a flow path for a raw material gas containing hydrogen and carbon monoxide or carbon dioxide, the raw material gas flowing into the honeycomb catalyst 100 through the flow holes 112 comes into contact with the catalyst components 130 supported on the surfaces of the partition walls 111, causing a methanation reaction. At this time, since the partition walls 111 are porous, the raw material gas passes through the partition walls 111 and moves to the adjacent through holes 112, so that the raw material gas easily comes into contact with the catalyst components 130 supported on the partition walls 111. In addition, since the outer peripheral surface of the honeycomb catalyst 100 is sealed by the coating layer 120, the raw material gas can be prevented from leaking out from the side surface of the honeycomb catalyst 100.
[0019] The material of the ceramic honeycomb structure 110 is not particularly limited, and can be appropriately selected from, for example, cordierite, mullite, SiC, Si·SiC, SiO2·SiC, Al2O3·TiO2, titanium oxide, silicon nitride, zeolite, aluminum oxide, or a composite of two or more of these, taking into consideration strength, cost, and thermal conductivity inside the honeycomb structure.
[0020] The cross-sectional shape of the through holes 12 in a plane perpendicular to the central axis of the ceramic honeycomb structure 110 is not limited to the substantially rectangular shape as shown in Fig. 1, and may be a substantially polygonal shape such as a triangle or a hexagon. By forming the ceramic honeycomb structure 110 into a structure in which the substantially polygonal through holes 112 are arranged, heat is physically conducted through the partition walls 111 between the adjacent through holes 112, and this has the effect of improving the thermal conductivity of the ceramic honeycomb structure 110. In addition, the outer peripheral shape of the ceramic honeycomb structure 10 is not particularly limited, but can be appropriately selected from approximately circular shapes such as a perfect circle or an ellipse, or approximately polygonal shapes such as a rectangle, a square, a triangle, a hexagon, or an octagon, depending on the shape of the reaction tube described later, so as to reduce the space between the honeycomb catalyst 100 and the reaction tube.
[0021] Moreover, the thermal conductivity of the coating layer 120 is 1.5 W / [m·K] or more. It is preferably 1.55 W / [m·K] or more. When the thermal conductivity of the coating layer 120 is high, the efficiency of dissipating the reaction heat generated by the methanation reaction of the honeycomb catalyst 100 is improved, and the temperature rise of the honeycomb catalyst 100 can be suppressed, so that the conversion rate of the raw material gas to methane is significantly improved. It is preferable that the coating layer 120 is dense. Specifically, it is preferable that the porosity is 60% or less. More preferably, it is 50% or less. Of course, the porosity of the coating layer 120 may be 0%. This is to prevent the raw material gas that has flowed into the honeycomb catalyst 100 from leaking out from the side surface of the honeycomb catalyst 100 before the methanation reaction.
[0022] The material for forming such a coating layer 120 may have a thermal conductivity of 1.5 W / [m·K] or more, and such a material is preferably an amorphous oxide matrix in which SiC particles are dispersed. More preferably, the amorphous oxide matrix is made of silica, alumina, or a composite material thereof. Alternatively, the material may be appropriately selected from cordierite, mullite, SiC, SiO2, or a composite material of two or more of these. By providing such a coating layer 120 with high thermal conductivity, a honeycomb catalyst 100 with high heat removal efficiency can be provided.
[0023] The catalyst component 130 is composed of a catalytically active metal and a catalyst carrier. The catalytically active metal preferably contains at least one of Ni, Fe, Co, Cu, and Ru. The carrier preferably contains at least one of alumina (Al2O3), ceria (CeO3), and zirconia (ZrO2). The honeycomb catalyst of the present invention, which has excellent heat removal efficiency, can be suitably used for exothermic reactions such as methanation reactions, so it is desirable that the catalyst component to be supported is one that can be used for methanation reactions.
[0024] As described above, the honeycomb catalyst of the present invention has a high heat removal efficiency due to the presence of a coating layer with high thermal conductivity on the outer periphery, and can efficiently remove the reaction heat generated by the catalytic reaction.
[0025] (Reactor) A second embodiment of the present invention is a reactor comprising: a ceramic honeycomb structure having a plurality of through holes separated by partition walls; a honeycomb catalyst having a catalyst component containing at least one of Ni, Fe, Co, Cu, and Ru supported on a surface of the partition walls, and a coating layer formed on an outer peripheral surface of the ceramic honeycomb structure, the coating layer having a thermal conductivity of 1.5 W / [m K] or more; and a reaction tube, in which the honeycomb catalyst is inserted into the reaction tube.
[0026] FIG. 2 shows an example of the methanation reactor of this embodiment. This is a single-tube shell-and-tube reactor, which is one form of a so-called isothermal reactor. The reactor 200 is configured by attaching a heat removal medium circulation jacket pipe 211 to the outer periphery of a reaction tube 210 for heat recovery, and inserting a honeycomb catalyst 100 into the reaction tube 210. By using a catalyst with high heat removal efficiency such as the honeycomb catalyst 100 in the reactor, the reactor 200 can be kept at a constant temperature, and the efficiency of the catalytic reaction can be improved. The reaction tube 210 may be one that has been installed in the line in advance. In such a case, by inserting the honeycomb catalyst 100 into the reaction tube 210, replacement and maintenance are easier than with conventional pellet-type catalysts.
[0027] The material of the reaction tube 210 is not particularly limited, but taking into consideration strength, cost, thermal conductivity, and the like, for example, stainless steel can be used.
[0028] In addition, when a space is generated between the reaction tube 210 and the honeycomb catalyst 100, it is preferable to provide a buffer material 220 in the space. The material of the buffer material 220 is more preferably a copper nonwoven fabric. By using a material with high thermal conductivity for the buffer material 220, the heat removal efficiency of the reactor 200 is less likely to decrease.
[0029] As described above, the reactor of the present invention uses a honeycomb catalyst with excellent heat removal efficiency, so that the temperature inside the reactor can be kept constant. This improves the efficiency of the catalytic reaction, which is an exothermic reaction.
[0030] (Manufacturing method of honeycomb catalyst) A third form of the present invention is a method for manufacturing a honeycomb catalyst, comprising the steps of applying a slurry liquid containing an inorganic binder to a ceramic honeycomb structure formed by firing and having a plurality of flow holes separated by partition walls, applying a slurry liquid containing a catalytic component, and then drying the resulting mixture to support the catalytic component on the partition walls, and applying a coating material comprising colloidal silica or colloidal alumina in which SiC particles are dispersed, onto the outer peripheral surface of the ceramic honeycomb structure on which the catalytic component is supported, to form a coating layer comprising amorphous silica or amorphous alumina in which SiC particles are dispersed.
[0031] The ceramic honeycomb structure used can be produced, for example, as follows. The material of the ceramic honeycomb structure 110 that is the substrate of the honeycomb catalyst 100 can be appropriately selected from cordierite, mullite, SiC, Si·SiC, SiO2·SiC, Al2O3·TiO2, titanium oxide, silicon nitride, zeolite, aluminum oxide, or a composite material of two or more of these materials. Here, a manufacturing method in which cordierite is used as the main phase will be described.
[0032] First, a clay is prepared as a raw material for the ceramic honeycomb structure 110. Powders such as kaolin, talc, silica, aluminum hydroxide, and alumina are adjusted to obtain a cordierite-forming raw material powder containing, by mass ratio, 47-53% SiO2, 32-38% Al2O3, 12-16% MgO, and 2.5% or less of unavoidably mixed components such as CaO, Na2O, K2O, TiO2, Fe2O3, PbO, and P2O5. Forming binders such as methylcellulose and hydroxypropylmethylcellulose, and pore formers made of graphite, synthetic resin, and the like are added to the cordierite-forming raw material powder, and a specified amount of water is poured in and mixed and kneaded sufficiently to produce a clay that can be plasticized.
[0033] Next, the clay is used to produce a ceramic honeycomb structure 110 having a plurality of through holes separated by partition walls. An extrusion die having a known structure is used to perform extrusion molding, and the obtained honeycomb structure molded body is dried to produce a dried honeycomb structure having a large number of through holes (cells) surrounded by partition walls 111. Thereafter, the dried body is fired to obtain the ceramic honeycomb structure 110 composed of a fired porous ceramic body.
[0034] Next, after processing and removing the outer periphery and both end faces, a slurry liquid containing an inorganic binder is applied to the fired body, and then a slurry liquid containing a catalyst component containing at least one of Ni, Fe, Co, Cu, and Ru is applied to the fired body, and then dried to obtain a ceramic honeycomb structure 110 in which the inorganic binder layer formed on the partition wall 111 supports the catalyst component 130. An example in which alumina is used as the inorganic binder and catalyst particles containing Ni are used as the catalyst component will be described below. First, a colloidal solution of commercially available alumina hydrate is adjusted to a desired concentration. The ceramic honeycomb structure 110 is immersed in this slurry liquid, and after removing excess slurry, it is dried and fired to adhere the alumina component to the ceramic honeycomb structure 110. Then, an aqueous solution of commercially available nickel (II) nitrate hexahydrate Ni(NO3)2·6H2O reagent is prepared, and the ceramic honeycomb structure 110 is immersed in this aqueous solution, dried, and fired to obtain the ceramic honeycomb structure 110 with NiO components attached to the porous alumina surface. Then, the ceramic honeycomb structure 110 is fired in a hydrogen atmosphere to reduce the NiO, and the ceramic honeycomb structure 110 with the Ni / Al2O3 components attached is obtained.
[0035] Next, a coating material in which SiC particles are dispersed in colloidal silica or colloidal alumina is applied to the outer peripheral surface of the ceramic honeycomb structure 110 carrying the catalyst component 130, and a process is performed to form a coating layer 120 in which SiC particles are dispersed in amorphous silica or amorphous alumina, to obtain a honeycomb catalyst 100. An example of forming a coating layer 120 in which SiC particles are dispersed in an amorphous silica matrix is described below. A methyl cellulose binder is added to SiC powder, and a specified amount of colloidal silica and water are added, and the mixture is thoroughly mixed and kneaded to prepare a plasticizable clay. This is applied to the outer peripheral surface of the ceramic honeycomb structure 110 as the coating layer 120, and then dried to obtain the honeycomb catalyst 100.
[0036] At this time, it is preferable to polish the outer peripheral surface of the ceramic honeycomb structure and both end faces through which the raw material gas flows in and out before supporting the catalyst component 130, because this makes it easier to accurately calculate the amount of catalyst component required to be supported relative to the weight or volume of the ceramic honeycomb structure and reduces the risk of supporting excess catalyst component. In addition, by polishing before supporting the catalyst component, the yield of the catalyst component can be improved. Furthermore, it is preferable to polish the outer peripheral surface of the ceramic honeycomb structure and both end faces through which the raw material gas flows in and out before forming the coating layer 120, since this improves the finishing accuracy of the outer diameter dimension of the honeycomb catalyst relative to the inner diameter of the reaction tube.
[0037] In this way, it is possible to provide a method for efficiently manufacturing a honeycomb catalyst having excellent heat removal efficiency.
[0038] Here, in order to ensure that the honeycomb catalyst has a structure suitable for improving thermal conductivity, samples 1 to 12 listed in Table 1 were prepared, and the effects on thermal conductivity of the materials of the ceramic honeycomb structure and coating layer, as well as the materials of the buffer material in a reactor using a honeycomb catalyst, as described below, were compared.
[0039] Next, the method for producing each sample will be described. All samples 1 to 12 were uniform in area, approximately 10 mm x 10 mm. Ceramic honeycomb structures were prepared with cordierite as the main component and SiC as the main component. Coating layers were prepared with SiO2 particles dispersed in an amorphous silica matrix and with SiC particles dispersed, respectively, and were formed on the ceramic honeycomb structures to a thickness of approximately 1.5 mm. After that, samples were cut out so that a coating layer with a thickness of approximately 1.5 mm and partition walls with a thickness of approximately 0.3 mm were laminated. The cushioning materials were asbestos heat-resistant sheet (Vermoflex (registered trademark) manufactured by Nichias Corporation), copper nonwoven fabric (fiber equivalent diameter: approximately 30 μm, basis weight: approximately 500 g / m2), and a 100% polyester resin. 3) were used. In addition, a stainless steel plate with a thickness of about 2.85 mm was prepared assuming the reaction tube 210 of the methanation reactor shown in Fig. 2. A honeycomb substrate including a buffer material and a coating layer was layered on this stainless steel plate in order to produce a laminated material sample simulating the cross-sectional structure of the honeycomb catalyst 100 inserted inside the methanation reaction tube 210.
[0040] These were combined in the configurations shown in Table 1 to produce Samples 3 to 12. Samples 1 and 2, which consisted of only the coating layer, were also prepared in order to compare the thermal conductivity of the coating layer itself. Samples 1 to 12 thus produced were pressurized with a load surface pressure of 1 MPa, and their thermal conductivity was measured at atmospheric pressure and room temperature using a temperature gradient method.
[0041] [Table 1]
[0042] Comparing Samples 1 and 2, which have only a coating layer, Sample 1, in which the coating layer material is an amorphous silica matrix with SiO2 particles dispersed, has a thermal conductivity of 0.46 W / [m·K], whereas Sample 2, in which SiC particles are dispersed in an amorphous silica matrix, has a thermal conductivity of 1.57 W / [m·K], indicating that samples with SiC particles dispersed have a higher thermal conductivity than samples with SiO2 particles dispersed. On the other hand, when comparing Samples 3 and 5 in which only the material of the ceramic honeycomb structure was changed, no significant difference was observed in the thermal conductivity. From this, it can be said that the effect of the material of the ceramic honeycomb structure 110 is small when aiming at improving the thermal conductivity. Furthermore, when comparing Samples 4 and 6, and Samples 5 and 7, in which only the coating layer material was changed, it is found that Samples 11 and 12, in which the coating layer material is SiC particles dispersed in an amorphous silica matrix, have significantly higher thermal conductivity. In other words, by using a coating layer with a thermal conductivity of 1.5 W / [m K] or more, as shown in Sample 2, it is possible to increase the thermal conductivity of the honeycomb catalyst and to expect improvements in heat removal efficiency. A comparison of Samples 4 and 5, which only differ in the material of the cushioning, and a comparison of Samples 6 and 7, shows that the thermal conductivity of Samples 5 and 7, which use copper nonwoven fabric as the cushioning material, is significantly higher. This suggests that copper nonwoven fabric, which has high thermal conductivity, can be suitably used as the cushioning material. [Explanation of symbols]
[0043] 100: Honeycomb catalyst 110: Ceramic honeycomb structure 111: Bulkhead 112:Flow hole 120: Coating layer 130: Catalyst components 200: Reactor 210: Reaction tube 211: Heat removal medium circulation jacket pipe 220: Cushioning material
Claims
1. a ceramic honeycomb structure having a plurality of through holes separated by partition walls; a catalyst component supported on a surface of the partition wall and including at least one of Ni, Fe, Co, Cu, and Ru; a coating layer formed on the outer peripheral surface of the ceramic honeycomb structure, A honeycomb catalyst, characterized in that the coating layer has a thermal conductivity of 1.5 W / [m·K] or more.
2. 2. The honeycomb catalyst according to claim 1, wherein the coating layer comprises a matrix made of an amorphous oxide and SiC particles dispersed in the matrix.
3. The honeycomb catalyst according to claim 2, wherein the amorphous oxide is amorphous silica or amorphous alumina.
4. a ceramic honeycomb structure having a plurality of through holes separated by partition walls; a catalyst component supported on a surface of the partition wall and including at least one of Ni, Fe, Co, Cu, and Ru; a coating layer formed on the outer peripheral surface of the ceramic honeycomb structure, A honeycomb catalyst having a thermal conductivity of the coating layer of 1.5 W / [m·K] or more; A reaction tube; wherein the honeycomb catalyst is inserted into the reaction tube.
5. 5. The reactor according to claim 4, further comprising a buffer material made of a copper nonwoven fabric provided between the reaction tube and the honeycomb catalyst.
6. a step of applying a slurry liquid containing an inorganic binder to the ceramic honeycomb structure having a plurality of through holes separated by partition walls formed by firing, applying a slurry liquid containing a catalyst component containing at least one of Ni, Fe, Co, Cu, and Ru, and then drying the applied slurry liquid to support the catalyst component on the partition walls; and applying a coating material having SiC particles dispersed in colloidal silica or colloidal alumina to the outer peripheral surface of the ceramic honeycomb structure carrying the catalyst component to form a coating layer having SiC particles dispersed in amorphous silica or amorphous alumina.
Citation Information
Patent Citations
Honeycomb structure
JP2012046417A
Cited By
Methane production reactor
WO2026205183A1